Sosialisasi Pengenalan TOEFL Sebagai Persiapan Studi Lanjut Pada Siswa-Siswi SMAN 4 Pematang Siantar - Manurung, Sri Maneni; Purba, Indra Pranata; Sitinjak, Lasmaria Tiodora Silviana; Aryani, Novia; Herman, Herman; Sinaga, Yanti Kristina; Sinurat, Bloner; Batubara, Junita (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2023)
The aim of this research is to explore and highlight the effectiveness of TOEFL introduction outreach activities at SMA N 4 Pematang Siantar. The research method used is a quantitative descriptive method. In the preparation stage, the location of the activity was determined after internal discussions of the research team, and permission from the school was obtained. Open materials, such as PowerPoint, laptops, and projectors, are carefully prepared. The implementation stage includes introductions, TOEFL material presentations, and question and answer sessions, while the evaluation stage includes giving reading tests to students. The results of outreach activities show effectiveness in preparing students to face the TOEFL exam. Active student participation, relevant questions, and understanding seen from the reading test results indicate that the objectives of this activity have been achieved. This research provides a basis for the development of similar programs in other schools. The success of this activity can be used as an example to improve students' understanding of TOEFL in the future. The TOEFL introduction socialization activity at SMA N 4 Pematang Siantar succeeded in achieving learning objectives and had a positive impact on class XII PMIA 1 students